Measurement and modeling of indoor off-body channel in the 9.5～10.5 GHz band - Shanhu HUANG; Jun SUN; Haofei CHANG; Wenjun LV; Qin YANG (物联网学报)
In order to explore the wireless propagation characteristics of high-frequency indoor off-body channel, off-body channel measurements were carried out on multiple typical indoor scenes in the 9.5～10.5 GHz frequency band.In terms of large-scale fading, through studying the path loss, it is found that the human body occlusion factor has a sine function relationship with the rotation angle, and a negative exponential relationship with the distance between the receiver and transmitter.Therefore, a new type of off-body channel loss model related to distance and angle was established, and the accuracy and applicability of the new model was proved based on the shadow fading.In terms of small-scale fading, by analyzing the linear correlation between path loss and root mean square (RMS) delay spread, a new type of RMS delay spreading model related to distance and angle was obtained.It proves that the greater the distance between the antenna at the transceiver end and the occlusion factor caused by the rotation of the human body, the more severe the path loss and multipath fading.The new channel model can be used to design the off-body link of the internet of things environment body area network (BAN), providing a theoretical and practical basis for the future design of indoor wireless communication systems.